EPILITHIC DIATOMS OCCURRING IN A STREAM WITH CLEAN WATER PROPERTIES (TAHAR STREAM, ELAZIG, TURKEY) - Sonmez, Feray; Sen, Bulent (Parlar Scientific Publications (P S P), 2019)
In the study, seasonal variations in species composition and seasonal growth dynamics in epilithic diatom association in Tahar Stream was studied for a period of a year. Tahar Stream is one of the important inflows of Keban Dam Lake that is the second largest dam lake of Turkey. Samplings were performed monthly at stations chosen in upper, middle and lower parts of the stream. A total of 41 diatom taxa all belonging to pennales were identified throughout the study. The genera Cymbella, Diatoma, Epithemia, Gomphonema, Navicula and Nitzschia were represented by more species than others. Cocconeis pediculus, Cymbella affinis, C. helvetica, Diatoma elongata, Fragilaria acus, Gomphonema intricatum, G. olivaceum, Navicula cryptotenella, N. radiosa, N. rhynchocephala, Nitzschia sigmoidea, Pseudostaurosira brevistriata and Ulnaria ulna were noticable diatoms with respect to frequency of occurrence and their abundance in epilithon. Variations in occurrence of diatom species and their abundance at stations were compared and discussed in relation to physical and chemical properties of stream water. The physicochemical values yielded that Tahar Stream has Class I Water Quality according to the Inland Water Quality Criteria. This finding is supported to some extent by the occurrence of certain clean water diatom species.
Keywords: Epilithon; epilithic diatom; seasonal succession; Tahar Stream; Turkey